(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The global environment is under massive pressure due to human industrialisation from centuries. It is clear that the environment sciences dispel the myths and helps understand the severe impact of climate change on human health. environment and human health our planet’s two greatest existential threats complement and amplify one another. Climate change is directly connected to the social determinants of health and accelerates existing health inequities. We should evolve the way to focus on environment savvy but today’s network of policies, process, governance and modes of understanding fuels unhealthy and environmentally destructive production and consumption. We must realise that climate change and health issues are interrelated to each other indelibly.